2011
DOI: 10.1007/s00403-011-1163-7
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles in dermatology

Abstract: Recent advances in the field of nanotechnology have allowed the manufacturing of elaborated nanometer-sized particles for various biomedical applications. A broad spectrum of particles, extending from various lipid nanostructures such as liposomes and solid lipid nanoparticles, to metal, nanocrystalline and polymer particles have already been tested as drug delivery systems in different animal models with remarkable results, promising an extensive commercialization in the coming years. Controlled drug release … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
133
0
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 198 publications
(139 citation statements)
references
References 142 publications
0
133
0
6
Order By: Relevance
“…Such propensity of nanoparticles biodistribution gives the opportunity to efficiently deliver drugs to the target cells without adverse effect to the surrounding healthy cells and tissues. The effectiveness of the biodistribution of drugs through the nanopathway could be of importance in the chemotherapeutic treatment of organs laden with MPS-localized tumors such as hepatocarcinoma and hepatic metastasis hepatic metastasis originating from digestive tract, bronchopulmonary tumors, gynecological cancers, primitive tumors and metastasis, myeloma, small cell tumors, and leukemia [56,57].…”
Section: Antitumor Drugs Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…Such propensity of nanoparticles biodistribution gives the opportunity to efficiently deliver drugs to the target cells without adverse effect to the surrounding healthy cells and tissues. The effectiveness of the biodistribution of drugs through the nanopathway could be of importance in the chemotherapeutic treatment of organs laden with MPS-localized tumors such as hepatocarcinoma and hepatic metastasis hepatic metastasis originating from digestive tract, bronchopulmonary tumors, gynecological cancers, primitive tumors and metastasis, myeloma, small cell tumors, and leukemia [56,57].…”
Section: Antitumor Drugs Deliverymentioning
confidence: 99%
“…The delivery systems of this new generation carrier take the advantages of an enhanced skin penetration potentials, surface functionalization, and depot effect with sustained drug release, thereby allowing targeting of specific cells. The treatment of various types of skin diseases could be revolutionized through the use of nanomaterials as the delivery systems [57].…”
Section: Dermatology Drug Deliverymentioning
confidence: 99%
“…Dermocosmetic based polymeric nanoparticles provide broad opportunities for preventing aging and skin care, as well as for dermatological affections such as psoriasis, acne, eczema, skin mycosis, and inflammations (Papakostas et al, 2011).…”
Section: Skinmentioning
confidence: 99%
“…Although, a transfollicular penetration of particles could be observed when the skin barrier was strongly disrupted [9], several other studies demonstrated that particles of this dimension do not pass the intact barrier of the hair follicles [5,15,16], Therefore, loading of the particles with a drug represents an efficient opportunity to transport the drug into the hair follicles provided that, after reaching the specific depth within the hair follicles, the drug is released from the particles to penetrate independently through the intact barrier of the hair follicles, as shown previously [17].…”
Section: Introductionmentioning
confidence: 99%